2015
DOI: 10.1186/s12871-016-0221-2
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex facilitates early recovery after surgery even in the absence of neuromuscular monitoring in patients undergoing laryngeal microsurgery: a single-center retrospective study

Abstract: BackgroundIn many countries, routine clinical anaesthesia does not always involve neuromuscular monitoring. In these clinical settings, the efficacy and safety of sugammadex use has not yet been confirmed. We investigated the efficacy and safety of sugammadex in the absence of neuromuscular monitoring.MethodsOne hundred and forty patients who underwent laryngeal microsurgery with the use of rocuronium as a neuromuscular blocking agent, without the use of a neuromuscular monitoring device, were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Dexmedetomidine (now available as a multi-source generic) has been shown to facilitate extubation for earlier PACU discharge [ 65 , 66 ] and mitigate postpartum depression [ 67 ], but, when combined with ketamine as a continuous infusion, may not yield lower opioid consumption or pain scores [ 68 ]. Sugammadex may shorten time to extubation and may accelerate bowel function recovery and shorter postoperative LOS as compared to reversal of neuromuscular blockade with neostigmine and glycopyrrolate [ 69 , 70 ]. For use as a local anesthetic by wound infiltration, liposomal bupivacaine (LB) may reduce opioid use and hospital LOS as well as promote earlier oral diet [ 71 , 72 , 73 ], but this effect may be procedure-specific [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dexmedetomidine (now available as a multi-source generic) has been shown to facilitate extubation for earlier PACU discharge [ 65 , 66 ] and mitigate postpartum depression [ 67 ], but, when combined with ketamine as a continuous infusion, may not yield lower opioid consumption or pain scores [ 68 ]. Sugammadex may shorten time to extubation and may accelerate bowel function recovery and shorter postoperative LOS as compared to reversal of neuromuscular blockade with neostigmine and glycopyrrolate [ 69 , 70 ]. For use as a local anesthetic by wound infiltration, liposomal bupivacaine (LB) may reduce opioid use and hospital LOS as well as promote earlier oral diet [ 71 , 72 , 73 ], but this effect may be procedure-specific [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have compared the outcomes of using different neuromuscular blocking drugs and their reversal agents in otorhinolaryngologic surgery [ 10 , 11 , 12 , 14 ]. Our study is the first to investigate the hourly consumption of sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sugammadex with deep neuromuscular block in elective laryngeal microsurgery (LMS) has been shown to improve intubation conditions and the surgical rating scale [ 10 ]. Sugammadex, used as a reversal agent, has also been shown to have significantly shorter extubation time and fewer tachycardia events in the post-anesthesia care unit (PACU) than pyridostigmine in elective LMS [ 11 ]. Moreover, other studies have shown that reversal with sugammadex results in less diaphragmatic failure [ 12 ] and less postoperative desaturation and hypoxemia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sugammadex has been reported to be superior at preserving haemodynamic stability than anticholinesterases, which have been the most commonly used NM blockade reversal agent to date. [15,16] Due to the fear of adverse effects from cholinesterase inhibitors, these have been associated with concomitant used of anticholinergic agents such as atropine or glycopyrrolate. [17,18] However, the combination of these 2 agents having different pharmacokinetic and pharmacodynamic properties cannot completely prevent their adverse effects nor maximize their desired effect.…”
Section: Discussionmentioning
confidence: 99%